MARKETING STRATEGIC PLANNING, PRICING, MARKETING OF EVENTS IN THE FIELD OF HIGH-TECH ENTERPRISES ENERGY SAVING - KASIAN, SERHII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The creation of regional centers of standardization in the field of distribution and use of energy flows of an alternative type contributes to the consistency of the quality of energy supply and logistics services of high-tech enterprises (HTP) and housing and communal services (housing). The integrated combination of the latest forms of marketing communications and logistics service is based on the interaction and interpenetration of important types of marketing activities of industrial enterprises during the movement of resource flows in global and regional value chains focused on sustainable development. Logistics service contributes to a fuller adaptation of the vector of goods supply of enterprises to the demands of potential segments of the target market. Innovative and technological development encourages the constant improvement of means and methods of communication support of logistics services. The implementation of a set of business opportunities aimed at creating joint high-tech projects in the areas of technology transfer and commercialization of innovations is possible through the comprehensive integration of education, science and business. Theoretical and methodological components of marketing strategic planning, pricing, organization of marketing of energy saving events at high-tech enterprises were investigated. It is determined that the budgeting of marketing communications, taking into account the integrated application of unconventional marketing communications tools, pricing methods that focus on demand and competition, contributes to good training and clarification to social and economic agents, authorities, and the public. The feasibility of using innovative energy-saving technologies based on alternative energy sources is explained. It has been established that marketing energy-saving values of high-tech enterprises lie in the formation of marketing values for consumers, which creates competitive advantages in faster and more complete satisfaction of consumer needs. The concept of "marketing value" is developed, which reflects the impact of relational tools of cholistic marketing on communication support and logistical support for interaction with economic agents, stakeholders, consumers, which leads to the intensive formation of marketing values among noted interaction entities. Marketing communication motivational and behavioral components of high-tech enterprises are highlighted. The marketing activity of “BIZON-TEH 2006” enterprise was analyzed, which has many years of experience in the agricultural market of Ukraine, is included in the TOP-3 of the largest distribution of seeds and fertilizers.